2022
DOI: 10.3390/mi13030485
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle Transport and Sedimentation in a Rhythmically Expanding Alveolar Chip

Abstract: Understanding the mechanism of particle transport and sedimentation in pulmonary alveolus is important for deciphering the causes of respiratory diseases and helping the development of drug delivery. In this study, taking advantage of the microfluidic technique, an experimental platform was developed to study particle behavior in a rhythmically expanding alveolar chip for a sufficient number of cycles. The alveolar flow patterns at different generations were measured for two cases with the gravity direction pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The approximate formula for C c when d p > 0.1 μm is C c = 1 + 2.52 λ / d p , where λ is the mean free path of the molecules in the fluid ( λ = 60 nm for air). 37 As the particle size increases, this factor approaches 1. Measurements showed that a fraction of the aerosols in this experiment were less than 0.5 μm in diameter (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approximate formula for C c when d p > 0.1 μm is C c = 1 + 2.52 λ / d p , where λ is the mean free path of the molecules in the fluid ( λ = 60 nm for air). 37 As the particle size increases, this factor approaches 1. Measurements showed that a fraction of the aerosols in this experiment were less than 0.5 μm in diameter (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, the tracer aerosols were nebulised from the aqueous solution suspended with fluorescent polystyrene microspheres; therefore, the observed concentrations of aerosol particles differed from those in the real respiratory tract. Recently, Zhu and colleagues [35][36][37] developed an alveolar chip with a single alveolus in which the trajectories of silver particles in the glycerol/water solution were recorded to simulate the aerosols in airflows. Nevertheless, they did not take into account passive breathing in the lung, and the single alveolus configuration only partially reproduced the particle deposition in the multigenerational respiratory bronchioles.…”
Section: Introductionmentioning
confidence: 99%